Do long-term foreign currency sovereign credit ratings positively affect bond and equity market efficiency in Africa?. (23rd December 2020) - Mutize, Misheck; Gossel, Sean J.
This study investigates the weak-form efficiency of long-term foreign currency denominated bonds and stocks in incorporating long-term foreign currency sovereign credit rating announcements in 19 African countries over the period of 1994 to 2014. The results of Ljung-Box Q autocorrelation, runs and variance ratio tests find that sovereign credit ratings do not significantly impact bond market efficiency. In contrast, stock markets show evidence of weak form efficiency implying that long-term sovereign credit ratings positively affect equities market efficiency in Africa.